Mobility of cytoplasmic, membrane, and DNA-binding proteins in Escherichia coli - Kumar, Mohit; Mommer, Mario Salvador; Sourjik, Victor (Biophysical journal, 2010)
Protein mobility affects most cellular processes, such as the rates of enzymatic reactions, signal transduction, and assembly of macromolecular complexes. Despite such importance, little systematic information is available about protein diffusion inside bacterial cells. Here we combined fluorescence recovery after photobleaching with numerical modeling to analyze mobility of a set of fluorescent protein fusions in the bacterial cytoplasm, the plasma membrane, and in the nucleoid. Estimated diffusion coefficients of cytoplasmic and membrane proteins show steep dependence on the size and on the number of transmembrane helices, respectively. Protein diffusion in both compartments is thus apparently obstructed by a network of obstacles, creating the so-called molecular sieving effect. These obstructing networks themselves, however, appear to be dynamic and allow a slow and nearly size-independent movement of large proteins and complexes. The obtained dependencies of protein mobility on the molecular mass and the number of transmembrane helices can be used as a reference to predict diffusion rates of proteins in Escherichia coli. Mobility of DNA-binding proteins apparently mainly depends on their binding specificity, with FRAP recovery kinetics being slower for the highly specific TetR repressor than for the relatively nonspecific H-NS regulator.